Optimization of roughing filtration unit for a handwashing wastewater recirculation point-of-use system - Olupot, Peter Wilberforce; Menya, Emmanuel; Jjagwe, Joseph; Wakatuntu, Joel; Románc, Franz; Hensel, Oliver (Water Science & Technology, 2022)
A downward roughing filter unit consisting of silica sand as the filter medium was optimized for performance towards removal of turbidity and suspended solids from handwashing wastewater. Design-Expert software was employed to optimize media particle size, filter depth, and flowrate. Linear and quadratic models were found to best fit the responses of turbidity and suspended solids removal, respectively. Particle size and flow rate were the only parameters with significant effects on removal of turbidity and suspended solids. Optimal conditions were found to be media particle size 0.6 mm, filter depth 12 cm, and flow rate 0.3 Lmin 1, corresponding to removal efficiencies of 62 and 67% for turbidity and total suspended solids (TSS), respectively, as predicted by the model. Validation of model at optimal conditions resulted in turbidity and TSS removal of 55 and 53%, respectively. Additionally, removal efficiencies of the roughing filter towards apparent colour, true colour, biochemical oxygen demand (BOD5), and chemical oxygen demand (COD) from handwashing wastewater were 56, 20, 32, and 5%, respectively. Overall, although turbidity of filtered water was .50 NTU, the reduction achieved by roughing filtration is a significant step in enhancing the performance of water treatment processes downstream, including filtration and adsorption by slow sand filters and activated carbon, respectively.
Keywords: Filtration; Handwashing; Recycling; Roughing filter; Wastewater